Calidad de vida de las personas con discapacidad intelectual beneficiarias del programa misión solidaria Manuela Espejo de la parroquia Zumba. Año 2015. - Núñez García, Sandra Elizabeth (2016)
The present research work had the purpose of evaluate the Quality of Life of people with intellectual disabilities who are beneficiaries from mission solidarity Manuela Espejo program, from parish Zumba, for this it stablished a field design, a fixed transversal, prospective, and bibliographic, I have used the survey technique with its instrument the questionnaire and the Manfred’s human scale that it was applied to 50 people with the support of their relatives in this researched work I obtained these results: discapacity grade from higher 41 to 100 with 74% and less of 41 with the 26%, people from 20 to 40 year old with the 46%, predominating the male gender with the 64%, unmarried single people with the 100%, having as primary prevalence instruction prevalence in a 48%, in terms of benefits received by the program have: technical aids the 74%, Human Development Bonus the 70%, housing solutions 2%, the medical attention received the 84%. Regarding the quality of life was determinate in two ways: being the individual form the 56% with quality of life deficient and the group form it found that the 100% of population in study had a deficient quality of life, reaching a coefficient of 6,83 points according Manfred´s human scale, so the author designed and executed the action plan in coordination with Asociación 12 de Enero, Hospital Zumba, and the family members responsible of their care. In conclusion the people with intellectual disabilities have a quality of life deficient in group form as a whole and individual in more than half of population in study. Was executed an action plan with educational activities, conferences, atelier and direct attention to the people with intellectual disabilities Keywords: Quality of Life, Intellectual Disabilities, Mission Solidarity Manuela Espejo Program